Molecular mechanisms of neuroprotective effect of rutin - Chunmei, Zhang; Shuai, Wang (Frontiers in Pharmacology, 2025)
Neurological diseases, including stroke, Alzheimer’s disease, Parkinson’s disease, and diabetic neuropathy, pose a significant global health burden. The rising incidence of these diseases, driven by factors including an aging population, lifestyle changes, and environmental influences, has intensified the urgent need for effective neuroprotective therapies. Rutin, a natural flavonoid glycoside widely distributed in various plants including buckwheat, citrus fruits, and onions, has garnered significant attention as a promising neuroprotective agent. This review comprehensively evaluates the current research on rutin’s multifaceted neuroprotective mechanisms, which encompass antioxidant, anti-inflammatory, anti-apoptotic, antidepressant, anticonvulsant, and analgesic effects, as well as its role in enhancing neural signal transduction, improving learning and memory, and protecting the blood-brain barrier. However, despite its broad spectrum of neuroprotective effects and favorable safety profile, the clinical application of rutin is currently limited by its relatively low bioavailability. To address this limitation and fully harness rutin’s therapeutic potential, future research should prioritize the development of innovative formulations designed to enhance its bioavailability.